Living and Robotic Dogs as Elicitors of Social Communication Behavior and Regulated Emotional Responding in Individuals with Autism and Severe Language Delay: A Preliminary Comparative Study. (2nd January 2019) - Silva, Karine; Lima, Mariely; Santos-Magalhães, André; Fafiães, Carla; de Sousa, Liliana
ABSTRACT: The inclusion of animals and robots in therapeutic interventions for Autism Spectrum Disorder (ASD) has become more common. This study provides a first comparison between the potential of living versus robotic dogs to elicit social communication behavior and regulated emotional responses in individuals with ASD. Ten children and thirteen adults with ASD and severe lan- guage delay were tested for appropriate social communication behavior and cardiac autonomic functioning during a planned, structured interaction with an experimenter alone (no-stimulus condition), an experimenter accompanied by a living dog (dog condition), and an experimenter accompanied by a robotic dog (robot condition). A within-subjects design was followed to expose all participants to all three experimental conditions. Overall, participants (children and adults) showed a higher percentage of appropriate social behaviors in Living and Robotic Dogs as Elicitors of Social Communication Behavior and Regulated Emotional … the dog and the robot conditions than in the no-stimulus condition. In children, the living dog was more effective than the robotic dog in promoting social communication behavior. In adults, no such difference was found between the dog and the robot condition. Only the dog appeared to elicit a positive effect in cardiac autonomic functioning by increasing heart rate variability (HRV) and buffer- ing the decrease in parasympathetic activity due to interaction with the experimenter. The data are preliminary but relevant and warrant replication in larger-scale studies.